Systematic Review and Meta-Analysis of Randomized, Controlled Trials on the Effect of Exercise on Serum Leptin and Adiponectin in Overweight and Obese Individuals - Yu, Na; Ruan, Yuting; Gao, Xiaoyan; Sun, Jia (Hormone and Metabolic Research, 2017)
Previous reports have shown that exercise improves serum leptin and adiponectin abnormalities in overweight and obese individuals; however, results to date are controversial. Here we performed a systematic review and meta-analysis of the available randomized controlled trials (RCTs) of the possible beneficial action of exercise on serum leptin and adiponectin levels in overweight and obese individuals. We searched PubMed, EMbase, The Cochrane Library, and the Clinicaltrial.gov databases for relevant studies published between January 1980 and September 2015. Two independent reviewers extracted relevant data and assessed study quality and risk of bias. Data were pooled using a random-effects model for leptin and a fixed-effects model for adiponectin. Effect of size was expressed as mean difference (MD) with 95% confidence interval (CI). Heterogeneity was assessed (Cochran Q-statistic) and quantified (I 2 ). Twenty-eight RCTs (40 studies) were identified, of which 24 were on the effects of exercise on leptin (n=1 358) and 31 referred to changes in adiponectin (n=1 774). Our analysis revealed that exercise significantly reduced serum leptin (MD=−2.24 ng/ml; 95% CI, −3.26, −1.23; p<0.001) and increased adiponectin (MD=0.44 μg/ml; 95% CI, 0.13, 0.75; p=0.005) levels compared to no exercise as well as control (who were also overweight or obese). Exercise, particularly aerobic exercise, had a significant effect on serum leptin and a possible influence on adiponectin levels, suggesting its therapeutic implications.
Keywords: obesity; overweight; exercise; leptin; adiponectin